Public Sector Financial Management for Sustainability and SDGs in Europe
XXIII, 136 p. 20 illus.
Keywords: This book analyses the implications of sustainability on public financial management in Europe. Public sector entities at national, regional, and municipal levels all have an important role to play in achieving sustainable development, and are developing strategies to reach this goal. These plans are usually guided by the UN's Sustainable Development Goals and involve public financial management systems, which are adapting to the demanding requirements of meeting these challenges. This book investigates how public financial management systems have been influenced by requirements for sustainability in Europe. It assesses multiple aspects linked to public financial management, including budgeting, accounting, reporting, and auditing. It also considers the impact of the SDGs on accounting systems, as well as other issues related to sustainability, such as green budgeting, gender budgeting, and sustainability and environmental reporting. By providing a cross-country comparison, it aims to identify similarities and differences across Europe. The book will appeal to scholars and students of public policy and financial management, as well as those interested in sustainability and the SDGs. Marco Bisogno is Associate Professor of Accounting at the University of Salerno, Italy. Isabel Brusca is Professor of Accounting at the University of Zaragoza, Spain. Eugenio Caperchione is Professor of Public Management and Public Sector Accounting at the University of Modena and Reggio Emilia, Italy. Sandra Cohen is Professor of Accounting at Athens University of Economics and Business, Greece. Francesca Manes Rossi is Professor of Accounting at the University of Naples Federico II, Italy.